2015
DOI: 10.1039/c4nr05268d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-like BN/gelatin nanobiocomposites for gas barrier applications

Abstract: We report a simple, effective and green way for the fabrication of gelatin-graphene-like BN nanocomposites for gas barrier applications. The reinforcement effect of graphene-like BN on the gelatin properties is discussed. The obtained graphene-like BN nanocomposites show good dispersion in the gelatin matrix and remarkable capability to improve the crystallinity and the barrier properties of gelatin. The barrier properties of gelatin/BN nanocomposites have been enhanced by a factor of 500 at 2 bar compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 35 publications
0
70
0
Order By: Relevance
“…Nevertheless, LPE has been applied to a wide range of 2D materials including graphene, 19,31,32 BN, 3 TMDs, 20,33 TMOs, 34,35 GaS, 36 phosphorene 37, 38 and MXenes. 45 These structures have been used in a wide range of applications from barrier composites 46,47 to battery electrodes 48 to photodetectors. 26,40 The resultant dispersions can very easily be processed into nanostructured materials by a range of methods such as spray casting, 41 inkjet printing, 42,43 gravure printing 44 and freeze drying.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, LPE has been applied to a wide range of 2D materials including graphene, 19,31,32 BN, 3 TMDs, 20,33 TMOs, 34,35 GaS, 36 phosphorene 37, 38 and MXenes. 45 These structures have been used in a wide range of applications from barrier composites 46,47 to battery electrodes 48 to photodetectors. 26,40 The resultant dispersions can very easily be processed into nanostructured materials by a range of methods such as spray casting, 41 inkjet printing, 42,43 gravure printing 44 and freeze drying.…”
Section: Introductionmentioning
confidence: 99%
“…[7] PVDF is currently used for technical applications including protective coatings for the chemical industry and piping, where both chemical resistance and low friction responses are highly desirable properties. [14,15] The incorporation of NPs is typically hindered by agglomeration mechanisms and macro-defects formation at the polymerparticle interface, [16] leading to premature degradation of the materials and often limited long term performance. To date, only a hand-full of papers have been dedicated to investigating the changes in mechanical properties of PVDF upon inclusion of nano-fillers, which is primarily due to the difficulty to control the incorporation of largely hydrophilic NPs across such low surface energy material.…”
Section: Introductionmentioning
confidence: 99%
“…38,[43][44][45] One of the most important applications of 2D fillers in polymer-based composites are as barrier materials to reduce the permeability of the material to gases. 53 Recently, it has been reported that solution processing can be used to mix h-BN with a range of materials, including gelatin, cellulose, chitosan and soy protein, [54][55][56][57] resulting in improvements in their barrier properties. 46 Due to their low cost, high aspect ratio and low toxicity, nanoclays have been well-studied as barrier-enhancing fillers for polymers.…”
Section: Introductionmentioning
confidence: 99%